(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the methodology for developing speed physical qualities of students (18-22 years old) engaged in table tennis. The research developed a system of exercises aimed at developing the main types of speed — movement speed, reaction speed, maximum speed and special speed. In the experimental group, a special methodology was applied — a combination of interval method, repeated method, circuit training and special exercises for developing reaction speed. The research results showed that in the experimental group, speed indicators significantly improved compared to the control group: 30 m run improved by 11.8%, reaction speed — by 29.4%, "herringbone run" — by 12.2%, stroke speed — by 18.6%. The developed methodology serves to improve the speed training of students engaged in table tennis.